Preferences of patients with cancer for psychological counseling: a cross-sectional study using full-profile conjoint analysis in Japan. Issue 3 (13th July 2022) - Ichikura, Kanako; Shimizu, Sayuri; Oshima, Noriko; Ariizumi, Yosuke; Fujie, Toshihide; Yamauchi, Shin-ichi; Ishikawa, Toshiaki; Nakajima, Yasuaki; Fukase, Yuko; Murayama, Norio; Murase, Hanako; Tagaya, Hirokuni; et al.
Abstract: Background: Psychological counseling is an effective nonpharmacological intervention for patients with cancer experiencing psychological distress. This study used a conjoint analysis approach to assess the preferences of patients with cancer for psychological counseling. Methods: We conducted a single-center, cross-sectional study using a self-report questionnaire. Data were collected from outpatients and inpatients in the departments of respiratory medicine, gastrointestinal surgery, female pelvic surgery, and head and neck surgery at a university hospital between March 2018 and March 2020. The questionnaire was developed using semistructured interviews with 10 clinical psychologists. It included 48 scenarios to determine patients' preferences for counseling based on a combination of the type, length, cost, and frequency of counseling. We performed a conjoint analysis, calculating the relative importance and part-worth utility value of each factor. Results: The results of the conjoint analysis showed that patients with cancer considered counseling type as the most important factor (relative importance: 37.5%), followed by frequency (23.4%), cost (19.6%), and length (19.5%). Patients with cancer valued life reviews more highly than problem-solving, emotional control, and emotional expression. However, women and younger patients valued counseling for emotional control the most, and patients with advanced cancer valued counseling for problem-solving the most. Conclusions: The results suggest that patients with cancer consider the type and content of counseling to be the most important factors in their decision process, although these preferences vary with individual characteristics. This is the first study to clarify the preferences of patients with cancer for psychological counseling using a conjoint analysis, and it proposes a new economic approach in the field of psycho-oncology.